THE EFFECT OF DISTRACTION TECHNIQUES ON ANXIETY LEVELS IN PREGNANT WOMEN ABOUT THE PROCESS OF LABOR IN WONOGIRI - Husna, Putri Halimu; Astuti, Retno Dwi Puji (Akademi Keperawatan Giri Satria Husada Wonogiri, 2018)
Background: Anxiety was a condition of emotions and subjective experiences of individuals towards objects that were not clear and specific due to the anticipation of danger which allows individuals to take action to face threats. Anxiety in pregnant women was very risky because it could cause death to both the mother and the fetus. The distraction technique was expected to reduce the anxiety level of pregnant women.Purpose: The purpose of this study was to reduce the level of anxiety in pregnant women who are facing childbirth.Methods: This research used a qualitative study with a case study research approach. The number of respondents was 3 pregnant women with 3rd trimester of pregnancy. The sampling technique used a cluster random sampling technique. Collecting data using interviews, observation, and measuring the level of anxiety before and after giving distraction techniques. The instrument used in this study was the Hamilton Anxiety Rating Scale (HARS) questionnaire.Results: The results of the study showed that the level of anxiety of the informants before the treatment was informant 1 with a score of 21, informant 2 with a score of 21, informant 3 with a score of 25. The level of anxiety of the informants after the treatment was informant 1 with a score of 13, informant 2 with a score of 12, informant 3 with a score of 13.Conclusion: The conclusion of this study shows that the anxiety level of the three respondents is resolved by the distraction technique, there is a decrease in the level of anxiety after giving the distraction technique.